2002
DOI: 10.1021/jf010832w
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Fatty Acid and Triacylglycerol Composition of the Oil of Coconut (Cocos nucifera L.) Hybrids and Their Parentals

Abstract: The fatty acid profiles and triacylglycerol (TAG) compositions of oils from the solid endosperm of different Philippine coconut hybrids and their parentals were determined by using gas chromatography (GC) and high-performance liquid chromatography (HPLC). In general, varietal differences in fatty acid composition were observed. Lauric acid (C12) content was significantly higher in the hybrids PCA 15-8 (50.45%) and PCA 15-9 (50.26%) by about 3.16% points as compared to other hybrids, and higher in Tacunan Green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 6 publications
5
53
0
12
Order By: Relevance
“…Gas chromatographic analysis of coconut oil has been reported for various purposes using various derivatization methods including base catalyzation [10], acid catalyzation [11] and acid trifluoride catalyzation [12], but no one give special attention on the derivatization methods. There is no report on the medium fatty acid derivatization including their kinetic of reaction and the efficiency compared to derivatization of other longer fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatographic analysis of coconut oil has been reported for various purposes using various derivatization methods including base catalyzation [10], acid catalyzation [11] and acid trifluoride catalyzation [12], but no one give special attention on the derivatization methods. There is no report on the medium fatty acid derivatization including their kinetic of reaction and the efficiency compared to derivatization of other longer fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Rossell et al (1985) and Laureles et al (2002) have reported lauric acid values of 45.9-50.3%, and 47.3-52.6%, respectively, for coconut oil from the Philippines (46.2-48.7%), Papua New Guinea (47.1-50.3%), Vanuatu (47.1-48.4%), North Sulawesi (45.9%) and Sri Lanka (49.3-52.6%) (Rossell et al, 1985;Laureles et al 2002). In this study the lauric acid value of all the UCNOs (49.11 to 51.66%) and RBDCNO (50.90%) of Indian origin were comparable with the results reported by Rossell et al, (1985) and Laureles et al (2002). But, the VCNO showed a significantly higher lauric acid content (55.75%) as compared to UCNOs and RBDCNO.…”
Section: Physicochemical Characteristics Of Different Types Of Coconumentioning
confidence: 99%
“…Coconut oil is one of such SFA carriers constituting an important source of saturated medium chain fatty acids, i.e. lauric acid C12:0 and myristic acid C14:0 (Laureles et al, 2002). These acids were identified as substances strongly reducing microorganisms participating in methanogenesis (Dohme et al, 1999;Machmüller et al, 2003a).…”
Section: Saturated Fatty Acidsmentioning
confidence: 99%